Madrasah Committee: Implementation of “Merdeka Belajar” ‎and The Progress of Islamic Education in Pamekasan - Supandi; M. Sahibuddin; Untung; Akhmadul Faruq (State Islamic Institute of Madura, 2024)
The madrasa committee is an independent institution formed by educational institutions to have a role in improving the quality and services of education in the form of direction, support for both educational facilities and infrastructure, and supervision of the implementation of education in each education unit. The madrasa committee plays a role as an Education Advisory, Education Supporting, Education Mediatory, and even controlling the implementation of Education itself. We must carry out the policy of